1976
DOI: 10.1203/00006450-197601000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Regulation in Isolated Perfused Near Term Monkey Liver

Abstract: ExtractGlycogen metabolism was studied in the isolated perfused liver of the monkey conceptus at 90% of gestation using an in situ recirculating perfusion system. Net uptake of glucose and galactose and the activities of the enzymes, glycogen synthetase and phosphorylase, were studied in response to varied perfusate composition. Synthetase activity was expressed as %I, the percentage of total synthetase activity in the active form. Perfusate glucose concentrations a s high as 700 mg/ 100 ml did not lead to net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…The demonstration of increasing response to glucagon mJechon with advancing gestational age is also consistent with acute glucagon-stimulated glycogenolysis as liver glycogen content increases rapidly between 110 days and term in the fetal sheep (25). Enzymes necessary for glycogen synthesis as well as degradation are also present at this stage of gestation in the fetal sheep (3) as well as in other species (26). Increasing hepatic responsivity to glucagon, particularly with regard to hepatic adenyl cyclase activation (30) may also be important.…”
Section: Discussionsupporting
confidence: 48%
“…The demonstration of increasing response to glucagon mJechon with advancing gestational age is also consistent with acute glucagon-stimulated glycogenolysis as liver glycogen content increases rapidly between 110 days and term in the fetal sheep (25). Enzymes necessary for glycogen synthesis as well as degradation are also present at this stage of gestation in the fetal sheep (3) as well as in other species (26). Increasing hepatic responsivity to glucagon, particularly with regard to hepatic adenyl cyclase activation (30) may also be important.…”
Section: Discussionsupporting
confidence: 48%
“…It has been well demonstrated that the fetal and neonatal liver can convert galactose to glycogen leading to net glycogen synthesis faster than they convert glucose to glycogen (19,20). The newborn liver converts galactose to glucose-1-phosphate faster in the suckling period than the adult period (21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations from our laboratory and other laboratories have demonstrated enhanced incorporation of galactose into glycogen when compared with glucose (2,3,6). Additional investigations have demonstrated that hepatic galactose uptake exceeds that for glucose in vitro, whereas activation of hepatic glycogen synthase and inactivation of glycogen phosphorylase was greater in the presence of galactose than that for glucose (5,6).…”
mentioning
confidence: 89%
“…precursor for neonatal hepatic glycogen synthesis (2)(3)(4)(5)(6). Previous investigations from our laboratory and other laboratories have demonstrated enhanced incorporation of galactose into glycogen when compared with glucose (2,3,6).…”
mentioning
confidence: 94%